1979
DOI: 10.2134/agronj1979.00021962007100050028x
|View full text |Cite
|
Sign up to set email alerts
|

Forage Quality of Prostrate Kochia Compared with Three Browse Species1

Abstract: Prostrate kochia [Kochia prostrata (L.) Schrad.], a shrub native to Asia, has received considerable attention because of its adaptation as a browse plant on western ranges. Prostrate kochia is a member of the Chenopodiaceae, the same family to which halogeton [Halogeton glomeratus (Bieb.) C. A. Mey.] and greasewood [Sarcobatus vermiculatus (Hook.) Torr.] belong. Both of these accumulate oxalates and can be toxic, depending on environmental conditions. This report presents data comparing crude protein, crude fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 5 publications
1
18
1
Order By: Relevance
“…] (Mosyakin 2003). The latter is a long-lived woody shrub native to the Asiatic region of Russia (Davis 1979), and is recognized as a potential forage plant in several western USA states (Mosyakin 2003;Lee et al 2005). Kochia prostrata has recently escaped or naturalized in Utah and adjacent states (Mosyakin 2003), but does not possess the annual weedy characteristics of K. scoparia.…”
Section: Description and Account Of Variationmentioning
confidence: 99%
“…] (Mosyakin 2003). The latter is a long-lived woody shrub native to the Asiatic region of Russia (Davis 1979), and is recognized as a potential forage plant in several western USA states (Mosyakin 2003;Lee et al 2005). Kochia prostrata has recently escaped or naturalized in Utah and adjacent states (Mosyakin 2003), but does not possess the annual weedy characteristics of K. scoparia.…”
Section: Description and Account Of Variationmentioning
confidence: 99%
“…Waldron et al (22) reviewed forage kochia's livestock grazing attributes. Nutritive properties include high CP (> 7%) during the critical fall/winter grazing period (1,2,23), low non‐toxic levels of oxalates (1), acceptable digestibility (2,23,24), ability to increase rate of digestion of low quality forage (22), and high palatability to cattle (21). Waldron et al (23) recently documented that cattle grazing forage kochia during winter maintained or improved body condition without any additional protein supplementation, resulting in a 25% economic savings over alfalfa hay feeding practices.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, Waldron et al (2006) recently reported that cattle grazing Immigrant forage kochia during the fall and winter maintained or improved body condition without any additional protein or nutrient supplementation. Its desirable forage nutritive properties were reviewed by Waldron et al (2010) and include high CP (>7%) during the critical fallwinter grazing period (Davis, 1979;Davis and Welch, 1985;McKell et al, 1990;Waldron et al, 2006), low nontoxic levels of oxalates (Davis, 1979), acceptable digestibility (Welch and Davis, 1984;McKell et al, 1990;Waldron et al, 2006), and increased rate of in situ dry matter and fi ber digestion of mixed diets containing forage kochia .…”
mentioning
confidence: 99%